1994
DOI: 10.1002/j.1460-2075.1994.tb06863.x
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of the Shigella flexneri Ipa invasins is activated by epithelial cells and controlled by IpaB and IpaD.

Abstract: Shigella species are enteropathogens that invade epithelial cells of the human colon. Entry into epithelial cells is triggered by the IpaB, IpaC and IpaD proteins which are translocated into the medium through the specific Mxi‐Spa machinery. In vitro, Shigella cells secrete only a small fraction of the Ipa proteins, the majority of which remains in the cytoplasm. We show here that upon interaction with cultured epithelial cells or in the presence of fetal bovine serum, S.flexneri release pre‐synthesized Ipa mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
358
0
6

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(388 citation statements)
references
References 36 publications
24
358
0
6
Order By: Relevance
“…During growth of bacteria in broth at 37 u C, the TTS apparatus is assembled in the bacterial envelope but is only weakly active (Menard et al, 1994a) and substrates of the TTS apparatus are stored in the cytoplasm in association with specific chaperones (Menard et al, 1994b; Niebuhr et al, 2000;Ogawa et al, 2003; Page et al, 2001Page et al, , 2002. The TTS apparatus is activated upon both contact of bacteria with epithelial cells (Menard et al, 1994a) et al, 1989) and transcription of an icsA-lacZ fusion carried by a reporter plasmid was decreased 2?5-fold in a virF mutant compared with the wild-type strain (Sakai et al, 1988), suggesting that expression of icsA was directly under the control of VirF. Northern blot analysis indicated that expression of icsA was moderately (2-fold) modulated by the temperature of growth (Porter & Dorman, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During growth of bacteria in broth at 37 u C, the TTS apparatus is assembled in the bacterial envelope but is only weakly active (Menard et al, 1994a) and substrates of the TTS apparatus are stored in the cytoplasm in association with specific chaperones (Menard et al, 1994b; Niebuhr et al, 2000;Ogawa et al, 2003; Page et al, 2001Page et al, , 2002. The TTS apparatus is activated upon both contact of bacteria with epithelial cells (Menard et al, 1994a) et al, 1989) and transcription of an icsA-lacZ fusion carried by a reporter plasmid was decreased 2?5-fold in a virF mutant compared with the wild-type strain (Sakai et al, 1988), suggesting that expression of icsA was directly under the control of VirF. Northern blot analysis indicated that expression of icsA was moderately (2-fold) modulated by the temperature of growth (Porter & Dorman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…During growth of bacteria in broth at 37 u C, the TTS apparatus is assembled in the bacterial envelope but is only weakly active (Menard et al, 1994a) and substrates of the TTS apparatus are stored in the cytoplasm in association with specific chaperones (Menard et al, 1994b;Niebuhr et al, 2000;Ogawa et al, 2003;Page et al, 2001Page et al, , 2002. The TTS apparatus is activated upon both contact of bacteria with epithelial cells (Menard et al, 1994a) and exposure of bacteria to the dye Congo red (Bahrani et al, 1997;Parsot et al, 1995). The TTS apparatus is deregulated, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Ipa sequences do not contain classical signal peptide sequences (4,7), the IpaB, IpaC, and IpaD proteins can be secreted onto the bacterial surface and released into the external medium, but only when the Mxi and Spa functions are expressed (1,2,6,8,9). Release of Ipa proteins into the external medium is triggered upon contact of the bacterium with the epithehal cells (10)(11)(12), and the released Ipa proteins form high molecular matrix structures (13).…”
mentioning
confidence: 99%
“…A maioria dessas funções está relacionada a proteínas codificadas por um fragmento de 31Kb do plasmídio de virulência formado por 38 genes. Entre esses genes estão ipaA, ipaB, ipaC, ipaD (responsáveis pela invasão, sobrevivência intracelular e escape bacteriano) VENKATESAN & BUYSSE, 1990;MENARD et al, 1993;MENARD et al, 1994a), ipgC (chaperona responsável pela estabilidade de ipaB e ipaC) (MENARD et al, 1994b), virB (proteína responsável para transcrição dos genes ipa e mxi-spa) , icsA, icsB (responsáveis pela disseminação celular e inibição da autofagia) (MAKINO et al, 1986;BERNARDINI et al, 1989;OGAWA et al, 2005), ospC1, ospF, ospG (responsáveis pela regulação da resposta imune do hospedeiro) (ZURAWSKI et al, 2006;KIM et al, 2008) e os genes do lócus mxi-spa (responsáveis pelo aparato do sistema de secreção do tipo III) (VENKATESAN et al, 1992;SASAKAWA et al, 1993;RATHMAN et al, 2000). O contato da bactéria com a superfície celular do hospedeiro induz à secreção dessas proteínas efetoras no interior de células hospedeiras, essenciais na sobrevivência bacteriana na célula do hospedeiro, conduzidas pelo sistema de secreção do tipo III (COSSART & SANSONETTI, 2004).…”
Section: E Coli Enteroinvasora (Eiec) E Coli Enteropatogênica (Epeunclassified